Development of Innovative Guidance Media Flipbook "Butterfly Hug" as a Strategy to Overcome Academic Stress of Students at State Vocational High School 4 Makassar - Khairun Annisa Jalil; Magfiratul Hidayah; Rili Palute; Fatimah Fatimah; Abdul Hakim (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2025)
Stress is a psychological and physiological condition experienced by individuals in response to stressors that are perceived as threatening, overwhelming, or exceeding personal coping abilities. In the school environment, stress frequently manifests as academic stress, which is commonly experienced by students in the adolescent age range of 15-18 years. Academic stress may arise from academic demands, pressure to achieve, evaluation systems, and interpersonal relationships at school. If not properly managed, academic stress can result in decreased academic performance, emotional imbalance, maladaptive behavior, and even hinder students’ future development. One effort that can be implemented to help reduce academic stress is cognitive therapy, including Butterfly Hug therapy, which is designed to facilitate relaxation, increase emotional regulation, and provide a sense of safety through independent practice. This study aims to describe the need for developing an innovative guidance media flipbook titled “Butterfly Hug” as a strategy to overcome academic stress among students at SMKN 4 Makassar. The research employed a research and development (R&D) approach. The results of the study show that the development of the flipbook media is strongly aligned with the needs of students and guidance and counseling teachers. The media is perceived as interesting, practical, and relevant to students’ psychological conditions. Furthermore, it has the potential to become an effective intervention tool in helping students recognize symptoms of academic stress, regulate emotions, and apply appropriate coping strategies.